2023
DOI: 10.3390/s23125555
|View full text |Cite
|
Sign up to set email alerts
|

HGR-ViT: Hand Gesture Recognition with Vision Transformer

Abstract: Hand gesture recognition (HGR) is a crucial area of research that enhances communication by overcoming language barriers and facilitating human-computer interaction. Although previous works in HGR have employed deep neural networks, they fail to encode the orientation and position of the hand in the image. To address this issue, this paper proposes HGR-ViT, a Vision Transformer (ViT) model with an attention mechanism for hand gesture recognition. Given a hand gesture image, it is first split into fixed size pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…This model recognized the input gesture model. These experiments confirmed that the proposed recognition model had good model performance in various data sets [5]. P. S. Neethu et al found that combination gestures were very complex and difficult for machines to classify.…”
Section: Related Worksupporting
confidence: 75%
“…This model recognized the input gesture model. These experiments confirmed that the proposed recognition model had good model performance in various data sets [5]. P. S. Neethu et al found that combination gestures were very complex and difficult for machines to classify.…”
Section: Related Worksupporting
confidence: 75%
“…Tan et al (2023) [ 14 ] introduced HGR-ViT, a Vision Transformer (ViT) model incorporating an attention mechanism designed for hand gesture recognition. The approach began by dividing a given hand gesture image into fixed-size patches.…”
Section: Related Workmentioning
confidence: 99%
“…They are also the most intuitive in a smart environment, as they can interact with devices as well as be universally used in various applications. User demands about hand gesture recognition have recently been continuously increased, and the research is being actively developed with regard to improving the gesture-recognition rate [ 7 , 8 ]. The hand gesture system is being applied to various devices, such as drones, robots, and smart home devices, as hand gesture recognition develops [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%